University–industry collaboration in a factor-driven economy: The perspective of Egyptian industry. Issue 3 (June 2017) - El Hadidi, Hala Helmi; Kirby, David A.
This is the fourth article in a series dealing with the role of universities in the innovation process in Egypt. The first three examined the topic from the perspective of academia. They revealed that there was relatively little university–industry collaboration. Hence, this article focuses on university–industry collaboration from the perspective of industry. It is based on a questionnaire survey of 237 firms located in different industrial zones in Cairo. The findings confirm the low level of university–industry collaboration, with no more than 6% of the sample claiming to have links with academia. The lack of collaboration is found to stem mainly from firms' perception that academic research is not relevant to them and from the mismatch between the interests and objectives of the two sectors. The article makes recommendations for what is needed if the situation is to change and focuses particularly on the role of government, the third actor in the Triple Helix.